2009
DOI: 10.1063/1.3231439
|View full text |Cite
|
Sign up to set email alerts
|

Broadband optical amplification in silicate glass ceramics containing Li2ZnSiO4:Cr4+ nanocrystals

Abstract: Transparent glass ceramics containing Li2ZnSiO4:Cr4+ nanocrystals are prepared and their optical properties are investigated. The glass ceramics show intense broadband infrared luminescence and long fluorescence lifetime of about 90 μs. The single-pass optical amplification is demonstrated on a traditional two-wave mixing configuration. The optical gain efficiency is about 1.27 cm−1 when the excitation power is 0.80 W. The optical gain shows the similar wavelength dependence with luminescence properties. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 19 publications
0
28
0
Order By: Relevance
“…Among TM ions, tetrahedrally coordinated Cr 4 þ [1,2], octahedrally coordinated Cr 3 þ [3,4] Bi ions in different valences and coordination states and octahedrally coordinated Ni 2 þ [5][6][7][8] can have broad emission bandwidths (typically4200 nm) in the near-infrared range from 1-1.7 μm. Ni 2 þ ions are mostly encountered in trigonal bipyramid and tetrahedral sites in oxide glasses [9][10][11], so that their emission efficiency is weak or non-existing in glasses compared to crystals.…”
Section: Introductionmentioning
confidence: 99%
“…Among TM ions, tetrahedrally coordinated Cr 4 þ [1,2], octahedrally coordinated Cr 3 þ [3,4] Bi ions in different valences and coordination states and octahedrally coordinated Ni 2 þ [5][6][7][8] can have broad emission bandwidths (typically4200 nm) in the near-infrared range from 1-1.7 μm. Ni 2 þ ions are mostly encountered in trigonal bipyramid and tetrahedral sites in oxide glasses [9][10][11], so that their emission efficiency is weak or non-existing in glasses compared to crystals.…”
Section: Introductionmentioning
confidence: 99%
“…So the broadband amplification in the whole telecommunication region by using only a single fiber would be expected to simplify the configuration of optical amplifiers and revolutionize the present telecommunication systems. Recently, we have demonstrated that Ni ions, 22),25),27),29) Cr 4+ ions 16) and PbS QDs 32) doped GCs are promising candidates for such application.…”
Section: Gcs For Nir Optical Amplificationmentioning
confidence: 99%
“…45 ions doped glass ceramic is also demonstrated for the first time. 16) Glass with composition of 48SiO 2 24Li 2 O16ZnO8Al 2 O 3 3K 2 O1P 2 O 5 0.1Cr 2 O 3 (mol %) was prepared. After two-step heat treatments at 540°C for 2 h and 700°C for 1 h, Li 2 ZnSiO 4 nanocrystals are formed inside the glass sample.…”
Section: Crmentioning
confidence: 99%
“…Transition-metal-doped nanostructured glasses, particularly silicates with Ni 2ϩ -and Cr 4ϩ -doped oxide nanocrystals, are currently investigated for the design of new broadband light-emitting devices, including fiber amplifiers, for the infrared spectral region~e.g., Zhou et al, 2007Zhou et al, , 2009Xu et al, 2008;Zhuang et al, 2009!. However, the design of a process for the fabrication of optical systems based on this class of materials has to take into account the critical treatment of glass nanostructuring.…”
Section: Introductionmentioning
confidence: 99%